Mobile application of popular restaurant in Kuantan, Pahang - Nor Sabrina, Barhanuddin (2018)
Nowadays, smartphones have become a very useful requirement for society. Almost everyone has their own smartphone and still affordable to have it although the price is not too cheap and not expensive. Furthermore, smartphones now have their own unique functions such as easy to search the information any time and everywhere compare to other. Other that, GPS, AR feature and Wi-Fi also have in feature of smartphone. This feature is suitable with this project which is using location navigation. In addition, nowadays our country was growing rapidly and make difficult to find curtain location because of the road factor especially the place that use the one-way road. This mobile application can help user get the right location navigation especially for the restaurant location. Most of the application are not have location navigation. Their just put information of the location. It gets hard to find especially for country that have using one-way road like Kuantan. If the user missed the place, it hard to go back because don’t have u turn way. This application is suitable to the tourist that travel in Kuantan and student who studying in Kuantan because they are not very familiar with the way in Kuantan. The purpose of this project to create an application of the popular and interesting restaurants in Kuantan for tourist that travel in Kuantan. The methodology that will be use in this project is waterfall model which include requirement analysis, design, implementation, verification and maintenance. The output of this application is to display the map navigation function of location user to the location restaurant popular in Kuantan. This app is expected to function as functional and provide useful information to users traveling to Kuantan, Pahang. Finally, multimedia combinations such as images, texts and sounds have been selected for use in this project to attract more users to this application.